Influence Akupresur At The Li 4 And Sp 6 To A Decrease In Pain Dysminorrhea - Ambarwati, Ambarwati; Pramudaningsih, Ica Narayani (Universitas Islam Lamongan, 2020)
Dysminorrhea causes physical symptoms and psychological symptoms. Each individual can experience physical symptoms and psychological symptoms at the same time, but can also experience only one of the symptoms, both physical and psychological. Signs of symptoms that can appear such as discomfort in the body, fatigue, nausea and vomiting, diarrhea, low back pain, headaches, sometimes accompanied by vertigo, feelings of anxiety, anxiety, to lose balance and lose patience to not be able to do activities it is done every day. Complementary acupressure therapy at points Li4 and Sp6 has the effect of reducing dysmenorrhea pain by pressing at certain points on the body (meridians) so as to get a stimulating effect on vital energy. The design used in this study is a quasi experimental research design with one-group pre-post test design. Subjects were observed for pain levels before and after the intervention using numerical rating scales. The population in this study were female students of Nursing Academy Krida Husada in the first and third semester, totaling 137 people. Samples taken in this study were 15 students who experienced dysmenorrhea on the first or second day during menstruation. The results of this study stated that the average pain scale before acupressure therapy in the experimental group was 5.4, and the average pain scale after acupressure therapy in the experimental group was 3.13. Wilcoxon test showed that there was a significant difference between pain scale before and after acupressure therapy in the experimental group with a p value of 0.001 (p <0.05).